Dal Disperso al Disperso: Kafka e le forme della narratività nel primo Maurizio Cucchi (ENTHYMEMA, 2020)
This study analyzes the relationship between Maurizio Cucchi’s first book of poems (1976) and Kafka’s The Man Who Disappeared. Kafka’s novel can be considered one of the main model for Cucchi’s Il disperso: starting from the title, the book seems to have influenced the Italian poet regarding both the themes – such as the relationship between the main character and his family or the building of an identity – and the forms of the writing. In particular, The Man Who Disappeared has represented to Cucchi an example of fragmented narration, characterized by diegetic holes and an incomplete structure. Through an intertestual comparison between the two books it will be possible to enlighten new aspects of Cucchi’s Il disperso, regarding his narrative features and his models.
Keywords: Maurizio Cucchi; Franz Kafka; The Man Who Disappeared; Italian contemporary poetry; contemporary lyric